Pterygium Prevention in Coastal Areas with The Use of Glasses - I Dewa Ayu Natih Canis Paloma; Ni Nyoman Geriputri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pterygium is a disorder on the surface of the eye whose cause is not fully known however, advanced age and exposure to ultraviolet (UV) light are often associated with risk factors for pterygium. A coastal environment that is windy, full of sunlight, dusty, and sandy is one of the factors that can cause pterygium. Prevention of pterygium is very important because untreated pterygium can cause blindness. The purpose of this paper is to find out how to prevent pterygium by using glasses and how to choose good glasses, especially in coastal areas. Study searches were carried out on several websites, such as PubMed and Google Scholar, with keywords such as